X‐ray fused with MRI guidance of pre‐selected transcatheter congenital heart disease interventions. Issue 3 (6th May 2019) - Grant, Elena K.; Kanter, Joshua P.; Olivieri, Laura J.; Cross, Russell R.; Campbell‐Washburn, Adrienne; Faranesh, Anthony Z.; Cronin, Ileen; Hamann, Karin S.; O'Byrne, Michael L.; Slack, Michael C.; Lederman, Robert J.; Ratnayaka, Kanishka
Abstract: Objectives: To determine whether X‐ray fused with MRI (XFM) is beneficial for select transcatheter congenital heart disease interventions. Background: Complex transcatheter interventions often require three‐dimensional (3D) soft tissue imaging guidance. Fusion imaging with live X‐ray fluoroscopy can potentially improve and simplify procedures. Methods: Patients referred for select congenital heart disease interventions were prospectively enrolled. Cardiac MRI data was overlaid on live fluoroscopy for procedural guidance. Likert scale operator assessments of value were recorded. Fluoroscopy time, radiation exposure, contrast dose, and procedure time were compared to matched cases from our institutional experience. Results: Forty‐six patients were enrolled. Pre‐catheterization, same day cardiac MRI findings indicated intervention should be deferred in nine patients. XFM‐guided cardiac catheterization was performed in 37 (median age 8.7 years [0.5–63 years]; median weight 28 kg [5.6–110 kg]) with the following prespecified indications: pulmonary artery (PA) stenosis ( n = 13), aortic coarctation ( n = 12), conduit stenosis/insufficiency ( n = 9), and ventricular septal defect ( n = 3). Diagnostic catheterization showed intervention was not indicated in 12 additional cases. XFM‐guided intervention was performed in the remaining 25. Fluoroscopy time was shorter for XFM‐guided intervention cases compared to matched controls. There was no significant difference in radiation dose area product, contrast volume, or procedure time. Operator Likert scores indicated XFM provided useful soft tissue guidance in all cases and was never misleading. Conclusions: XFM provides operators with meaningful three‐dimensional soft tissue data and reduces fluoroscopy time in select congenital heart disease interventions.